Defining the "core microbiome" of the microbial communities in the tonsils of healthy pigs - Lowe Beth A; Marsh Terence L; Isaacs-Cosgrove Natasha; Kirkwood Roy N; Kiupel Matti; Mulks Martha H (BMC Microbiology, 2012)
Abstract Background Porcine tonsils are the colonization site for many pathogenic as well as commensal microorganisms and are the primary lymphoid tissue encountered by organisms entering through the mouth or nares. The goal of this study was to provide an in-depth characterization of the composition and structure of the tonsillar microbial communities and to define the core microbiome in the tonsils of healthy pigs, using high throughput bar-coded 454-FLX pyrosequencing. Results Whole tonsils were collected at necropsy from 12 16-week-old finisher pigs from two healthy herds. Tonsil brushes were also used to collect samples from four of these animals. Bacterial DNA was isolated from each sample, amplified by PCR with universal primers specific for the bacterial 16S rRNA genes, and the PCR products sequenced using pyrosequencing. An average of 13,000 sequences were generated from each sample. Microbial community members were identified by sequence comparison to known bacterial 16S rRNA gene sequences. The microbiomes of these healthy herds showed very strong similarities in the major components as well as distinct differences in minor components. Pasteurellaceae dominated the tonsillar microbiome in all animals, comprising ~60% of the total, although the relative proportions of the genera Actinobacillus, Haemophilus, and Pasteurella varied between the herds. Also found in all animals were the genera Alkanindiges, Peptostreptococcus, Veillonella, Streptococcus and Fusobacterium, as well as Enterobacteriaceae and Neisseriaceae. Treponema and Chlamydia were unique to Herd 1, while Arcanobacterium was unique to Herd 2. Tonsil brushes yielded similar results to tissue specimens, although Enterobacteriaceae and obligate anaerobes were more frequently found in tissue than in brush samples, and Chlamydia, an obligately intracellular organism, was not found in brush specimens. Conclusions We have extended and supported our previous studies with 16S clone libraries, using 16S rRNA gene pyrosequencing to describe the microbial communities in tonsils of healthy pigs. We have defined a core microbiome, dominated by Pasteurellaceae, in tonsil specimens, and have also demonstrated the presence of unique minor components of the tonsillar microbiome present in each herd. We have validated the use of non-invasive tonsil brushes, in comparison to tonsil tissue, which will facilitate future studies.